Answer: the second option
explanation: below
Answer:
Step-by-step explanation:
To find the inverse of a function, simply switch the 'x' and 'y' variables. Substitute in 'y' in the place of f(x) for this purpose:
y = 2x - 10
Switch positions:
x = 2y - 10
Add '10' to both sides to begin simplifying:
x + 10 = 2y
Divide both sides by 2:
This can be rewritten as:
Therefore, the inverse of the function is:
If the base is 2 and the exponent is the the expression would look like this → 2³. In order to simplify it, you have to multiply the base number by the number of the exponent.
2×2×2=8
Therefore, the simplified expression would be 8.
I hope this helped.
Step-by-step explanation:
can u give image PlZzzzz ....